Differential antimicrobial susceptibility profiles between symptomatic and asymptomatic non-typhoidal Salmonella infections in Vietnamese children. (26th May 2020) - Parisi, Andrea; Le Thi Phuong, Tu; Mather, Alison E.; Jombart, Thibaut; Thanh Tuyen, Ha; Phu Huong Lan, Nguyen; Hoang Thu Trang, Nguyen; Carrique-Mas, Juan; Campbell, James I.; Glass, Kathryn; Kirk, Martyn D.; Baker, Stephen
Abstract: Non-typhoidal Salmonella (NTS) serovars, sequences types and antimicrobial susceptibility profiles have specific associations with animal and human infections in Vietnam. Antimicrobial resistance may have an effect on the manifestation of human NTS infections, with isolates from asymptomatic individuals being more susceptible to antimicrobials than those associated with animals and human diarrhoea.